Resource allocation and management in defence need for a framework - Ghosh, Amiya Kumar 1937- (KW Publishers in association with Centre for Air Power Studies, 2013)
The question that faces governments and militaries the world over is how best to allocate resources for management of defence in the new age. This book, by Shri A.K. Ghosh who has an economics background, explores the framework for change in resource allocation and capability building.